(untitled) - Varcarolis, Elizabeth M.; Elizabeth M. Varcarolis (St. Louis)
A pocket-sized clinical companion, Manual of Psychiatric Nursing Care Planning, 5th Edition supplies you with the latest diagnostic information available, including the DSM-5, for accurate assessment and diagnosis of patients. It offers quick and easy access to plans of care for a range of settings including the inpatient unit, home care, or community mental health setting. Expert author Elizabeth Varcarolis, provides a clinically-based focus with the latest guidelines to psychiatric nursing care. Designed to accompany Foundations of Mental Health Nursing, this book is a perfect reference for creating care plans and for clinical use
Includes bibliographical references and index
Keywords: Psychiatric nursing; Nursing care plans